2015
DOI: 10.1103/physrevb.92.134103
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic study of diffusion-mediated plasticity and creep using phase field crystal methods

Abstract: The nonequilibrium dynamics of diffusion-mediated plasticity and creep in materials subjected to constant load at high homologous temperatures is studied atomistically using Phase Field Crystal (PFC) methods. Creep stress and grain size exponents obtained for nanopolycrystalline systems, m 1.02 and p 1.98, respectively, closely match those expected for idealized diffusional NabarroHerring creep. These exponents are observed in the presence of significant stress-assisted diffusive grain boundary migration, indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Studies on Coble creep for bcc [27,29], fcc [30,31] and hcp [32] NC metals using molecular dynamics simulation have been reported in literature. The implication of stress-assisted grain boundary migration on diffusional creep deformation process has been investigated to some extent using atomistic simulations [33][34][35][36]. Creep behavior of nano joint using atomistic simulation is not studied till date although creep behavior study for brazing joints using continuum damage mechanics simulation [37,38] and combined creep-plastic behavior investigation of the interface between thermal barrier coatings and bond-coat using constitutive model are reported in literature recently [39].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies on Coble creep for bcc [27,29], fcc [30,31] and hcp [32] NC metals using molecular dynamics simulation have been reported in literature. The implication of stress-assisted grain boundary migration on diffusional creep deformation process has been investigated to some extent using atomistic simulations [33][34][35][36]. Creep behavior of nano joint using atomistic simulation is not studied till date although creep behavior study for brazing joints using continuum damage mechanics simulation [37,38] and combined creep-plastic behavior investigation of the interface between thermal barrier coatings and bond-coat using constitutive model are reported in literature recently [39].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has be shown that the method is derivable from the fundamental classical density functional theory (CDFT) [30,31], with certain approximations based on the Ramakrishnan and Yussouff [32] free energy formalism. Since its inception, the method has evolved to model structural phase transformations [33][34][35][36], alloy systems [30,37,38], multiferroic composite materials [39], order-disorder systems [40], nucleation and polymorphism [41,42], amorphous or glass transitions [43,44], quasicrystals [45] and crystal plasticity [46]. Through coarse graining procedures, the methodology may be used to generate models that operate on mesoscopic length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the operational cycles cause serious thermomechanical fatigues and creep-fatigue failures. An important source of inelasticity in the material structure is creep and viscoplasticity [1,2], which might be produced by microstructural changes [3,4]. Especially within such practical engineering materials, more than one damage mechanism might exist, such as the creepviscoplasticity interaction.…”
Section: Introductionmentioning
confidence: 99%